Membangun dakwah yang efektif sesuai instruksi Al-Qur’an - Athallah, Muhammad Farhan (Maliki Interdisciplinary Journal, 2024)
Da’wah is an important part that cannot be abandoned by Muslims. The success of da’wah will greatly determine the condition of the Muslim community and even give a good impression to bring about social change, changes in human character. To make da’wah a success, in this case the Qur’an is the main material for finding answers so that the da’wah is carried out effectively so that this da’wah can be accepted by all levels of humanity.